I carry you with me [videorecording (DVD)] - Ewing, Heidi E.; Espitia, Armando; Vázquez, Christian; Rodriguez, Michelle (Sony Pictures Home Entertainment, 2021)
Based on a true story, this decades-spanning romance begins in Mexico between an aspiring chef and a teacher. Their lives restart in incredible ways as societal pressure propels them to embark on a treacherous journey to NYC with dreams, hopes, and memories in tow.